Analisis Sentimen Opini Masyarakat Terhadap Pelayanan BPJS Kesehatan Provinsi Lampung Berbasis Twitter - Admi Syarif; Arafia Isnayu Akaf; Rizky Prabowo; Kurnia Muludi (Jurnal Pepadun, 2022)
Nowadays, the internet has increased the amount of information stored and accessed through the web at a very fast speed. The internet can be a place to express opinions on health topics, politics, companies, and others. Many social media are used by the people of Lampung in expressing opinions and seeking information. Twitter is one of the communication media that is in great demand by the public. There are various kinds of topics discussed by Twitter users, one of the topics that are currently being discussed is the Lampung Health Social Security Administration Agency (BPJS). Health is also a very important thing and is still a conversation that is often discussed anywhere and anytime. BPJS Health helps the community in overcoming a declining economy, with BPJS Health, the community does not have to pay for medical expenses. Therefore, the service from BPJS Kesehatan Lampung will be carried out by sentiment analysis so that it can be known whether the public opinion about BPJS Kesehatan Lampung is positive or negative. This study uses the NaÃ¯ve Bayes algorithm. This sentiment uses a dataset from Twitter which uses several keywords regarding BPJS Kesehatan Lampung. Based on the research results, it is known that the NaÃ¯ve Bayes algorithm has an accuracy value of 89,33%.